2008
DOI: 10.1007/s11127-008-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Wal-Mart reduce social capital?

Abstract: Wal-Mart, Social capital, Community, Retail, A10, A13, D00, Z1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…5 This information was obtained from http://walmartstores.com/AboutUs/ 7606.aspx, http://walmartstores.com/AboutUs/7605.aspx, and http://walmartstores.com/sites/AnnualReport/2009/financial_highlights.html. 6 More extensive reviews of the literature on Walmart can be found in Basker (2005b), Basker (2007), Hicks (2007), and Carden et al (2009a). 7 These different conclusions hinge on a methodological debate that we detail in Section 3.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…5 This information was obtained from http://walmartstores.com/AboutUs/ 7606.aspx, http://walmartstores.com/AboutUs/7605.aspx, and http://walmartstores.com/sites/AnnualReport/2009/financial_highlights.html. 6 More extensive reviews of the literature on Walmart can be found in Basker (2005b), Basker (2007), Hicks (2007), and Carden et al (2009a). 7 These different conclusions hinge on a methodological debate that we detail in Section 3.…”
Section: Theorymentioning
confidence: 99%
“…The data were used in Holmes (2008). 14 For examples, see Basker (2005a), Goetz and Rupasingha (2006), Goetz and Swaminathan (2006), Sobel and Dean (2008), and Carden et al (2009a), Carden et al (2009b). 15 We thank the Center for Disease Control for making the restricted data available.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Jottier and Heynelds (forthcoming) argue that social capital increases the benefits and lowers the cost of instrumental voting, thus increasing political accountability and government performance. Likewise, Putnam (1995), Poulsen and Svendsen (2005), Carden et al (2009) and Chong et al (2010aChong et al ( , 2010b view social capital as promoting social cooperation and worry about its development or deterioration.…”
Section: Introductionmentioning
confidence: 99%